Overview of Dysmenorrhea Severity and Management Choices amongFemale Medical Students at Universitas Mulawarman: 2024 Cohort - Kalya Natriswa Putri Kinanthi; Khairunnida Rahma (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : Dysmenorrhea, a highly prevalent gynecological complaint that significantly interferes with daily activities Objective : prompted this study to investigate the severity levels and treatment preferences among female medical students from